Effects of parent‐based social media and moderate exercise on the adherence and pulmonary functions among asthmatic children - Lin, Han‐Hong; Hung, Yi‐Ping; Weng, Shih‐Han; Lee, Pei‐Yi; Sun, Wei‐Zen (The Kaohsiung journal of medical sciences, 2020)
Our previous study showed Tai‐Chi‐Chuan (TCC) training, a moderate exercise, at school improved pulmonary function and inflammation profiles in children with mild asthma. However, habitual practice is hard to maintain with the lack of continuous family and peer support. We investigated whether parental intervention with social media could enhance children's adherence to exercise at home and improve asthmatic outcome measures. Parents were opted to attend a 12‐week TCC classroom training, supervise home practice, and report to a four‐step web‐based social media platform to stay updated and motivated through logging activity and tracking competition. Fractional exhaled nitric oxide (FeNO), FEV1/FVC and peak expiratory flow (PEF) were measured before and after 12 weeks of training. Fifty‐three asthmatic children were allocated into non‐TCC (control, n = 12), TCC groups with moderate‐to‐severe (TCC‐S, n = 26) and mild‐to‐moderate (TCC‐M, n = 15) asthma. We found both TCC groups exhibited better pulmonary function than the non‐TCC control. TCC increased FVC in mild‐to‐moderate asthma children while more pronounced improvement in FEV1, FEV1/FVC, PEF and FeNO was noticed in moderate‐to‐severe asthmatic children. All TCC subjects retained greater participation and better interaction online except for low‐ranking families who dramatically dropped their practice 9 weeks later. For asthmatic children, moderate exercise improves pulmonary functions in a severity‐dependent fashion. Parent‐based Learn‐Practice‐Persuade‐Award wheel is a useful platform to motivate children engagement in physical activity. Classical social persuasive skills could enhance general parent‐child relationship but tend to decrease in persuasiveness over time in low‐ranking families.